P-TSA-catalyzed one-pot synthesis of novel 7-aryl-6H-benzo[h][1, 3]dioxolo[4, 5-b]xanthene-5, 6(7H)-diones in ethanol. Issue 1 (2nd January 2017) - Qian, Kai; Fu, Zhijie; Cao, Xiaoji; Li, Sijun; Shen, Tianhua; Song, Qingbao
ABSTRACT: A one-pot, three-component reaction of aromatic aldehydes, 2-hydroxy-1, 4-naphthoquinone, and 3, 4-methylenedioxyphenol has been reported for the synthesis of novel 7-aryl-6H-benzo[h][1, 3]dioxolo[4, 5-b]xanthene-5, 6(7H)-diones using environmentally benevolent para -toluene sulfonic acid ( p -TSA) as the catalyst. This methodology provides a mild and fast route to diverse pyran derivatives in moderate to good yields. GRAPHICAL ABSTRACT: